Allocative Efficiency: The Role of Human Capital - Huffman, Wallace E. (Quarterly Journal of Economics, 1977)
I. Introduction, 59.—II. The model, 62.—III. Empirical analysis, 66.—IV. Further implications, 74.—V. Conclusions, 77.—Appendix: data and sources, 77.